1996
DOI: 10.1037/0022-3514.71.4.796
|View full text |Cite
|
Sign up to set email alerts
|

Positive affect, negative affect, and social interaction.

Abstract: Two studies explored the relations of positive and negative affect (PA and NA) to social interaction. In Study 1, unacquainted dyads were surreptitiously videotaped as they participated in a 6-min interaction. Participants then evaluated the quality of the interaction. Independent observers also rated the videotaped interactions. Trait PA was positively related to both participant and observer evaluations of interaction quality. In Study 2, undergraduates kept diaries of their social interactions for 1 week. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
173
2
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(197 citation statements)
references
References 41 publications
(61 reference statements)
16
173
2
1
Order By: Relevance
“…Specifically, the expression of positive emotions and moods facilitated rewarding social interactions and positive social responses (e.g., Berry & Hansen, 1996;Harker & Keltner, 2001). Consistent with these findings, studies on social responses towards depressed people showed that they are more likely to elicit social rejection than non-depressed people (for a review, see Marcus & Nardone, 1992).…”
Section: Introductionsupporting
confidence: 67%
“…Specifically, the expression of positive emotions and moods facilitated rewarding social interactions and positive social responses (e.g., Berry & Hansen, 1996;Harker & Keltner, 2001). Consistent with these findings, studies on social responses towards depressed people showed that they are more likely to elicit social rejection than non-depressed people (for a review, see Marcus & Nardone, 1992).…”
Section: Introductionsupporting
confidence: 67%
“…Large majority of the studies that addressed determinants of daily variations in psychological responses relied on selfadministered questionnaires to record past activities, which presented difficulties in this research field. For example Clark and Watson [5,6] argue that no such relation exists between NA and social activity, which is an opposing view to other studies [1,3,4], while Volkers at al. [9] claim that is not possible to clearly infer how mood states are related to the time of the day which was concluded by a number of other reports.…”
Section: Study Of Mood Changes and Associated Factorscontrasting
confidence: 47%
“…Happy participants also liked the person they saw on videotape more than did unhappy ones. Berry and Hansen (1996) found that when participants were "accidentally" left alone with a fellow student, those high in trait PA liked their partner more than those low in trait PA. In another study, happy faculty were found to write relatively more favorable letters of recommendation, and happy undergraduates wrote relatively more positive recommendations for hypothetical employees (Judge & Higgins, 1998).…”
Section: Perceptions Memories and Judgments Of Othersmentioning
confidence: 99%
“…Second through eighth graders judged the happiest targets as the ones most likely to help (Perry, Perry, & Weiss, 1986), and undergraduates, no matter what mood they themselves were experiencing, judged the happiest targets as being more likable (Bell, 1978). Finally, in laboratory studies, when female students were left alone with a peer, the partners of the high PA women found the social interaction to be more enjoyable and of higher quality, and so did neutral observers of the interaction (Berry & Hansen, 1996); objective observers rated participants high in dispositional positive affect as evidencing stronger leadership while performing a management task (Staw & Barsade, 1993).…”
Section: Likabilitymentioning
confidence: 99%
See 1 more Smart Citation